2020
DOI: 10.1029/2019wr026144
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Physical Properties of Everglades Peat Soils Induced by Increased Salinity at the Laboratory Scale: Implications for Changes in Biogenic Gas Dynamics

Abstract: Saltwater intrusion due to sea level rise is a major concern for the Florida Everglades because it may induce shifts in ecosystem productivity and physical soil properties. However, the effects of saline water intrusion into the current carbon gas dynamics of the Everglades (particularly in terms of biogenic gas production and emissions, i.e., CH4 and CO2) are still uncertain. In this work, we present a laboratory‐based study to simulate how sea level rise may alter the physical properties (i.e., hydraulic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 86 publications
(102 reference statements)
0
9
0
Order By: Relevance
“…frontiersin.org 2019), microhabitat (Morris et al, 2015), and soil pore water chemistry (Kettridge and Binley, 2010;McCarter et al, 2019McCarter et al, , 2020Sirianni and Comas, 2020). Branham and Strack (2014) observed that the K s of Sphagnum peat (pristine peat) was strongly positively correlated with the macropore occurrence (pore diameter of 2000 μm; Spearman correlation > 0.8).…”
Section: Frontiers In Environmental Sciencementioning
confidence: 99%
“…frontiersin.org 2019), microhabitat (Morris et al, 2015), and soil pore water chemistry (Kettridge and Binley, 2010;McCarter et al, 2019McCarter et al, , 2020Sirianni and Comas, 2020). Branham and Strack (2014) observed that the K s of Sphagnum peat (pristine peat) was strongly positively correlated with the macropore occurrence (pore diameter of 2000 μm; Spearman correlation > 0.8).…”
Section: Frontiers In Environmental Sciencementioning
confidence: 99%
“…This difference suggests that freshwater peat soils have an increased degree of pore dilation (approximately three times on average) when exposed to salt compared to peat soils previously exposed to elevated salinity where pore dilation has already occurred (i.e., Figure 7a). Previous work investigating the pore dilation effect in Everglades peat soils (i.e., Sirianni & Comas, 2020) found that a threshold may exist at approximately 0.25 S m −1 where the peat matrix loses some of its ability to dilate further despite further increases in salinity level and may represent the initial stages of peat collapse. Considering that average field salinity conditions at Site 1 and Site 2 are markedly larger than this threshold (i.e., 3.9 and 0.95 S m −1 , respectively), it is reasonable to expect that peat soils at Site 1 and Site 2 would not dilate to the same degree as peat soils at Site 3 as they are in a more permanently deformed state due to previous cycles of pore dilation and subsequent pore compression (i.e., during periods of no inundation).…”
Section: Discussionmentioning
confidence: 99%
“…Pore dilation in peat soils has been observed in several previous laboratory and field experiments in relation to changes in peat pore water salinity (e.g., Dijk et al, 2016;Kettridge & Binley, 2010;Ours et al, 1997;Sirianni & Comas, 2020). The pore dilation effect is explained by the relation between ionic strength and electrical double layer charge density in humic substances.…”
mentioning
confidence: 87%
See 2 more Smart Citations